Visible Light Communication Systems Conception and VIDAS - Kumar, Navin (2012)
Visible Light Communication (VLC) using LEDs is emerging as a key technology for a ubiquitous communication system, because LED has the advantages of fast switching, long life expectancy, being less expensive and being visible light that is safe for the human body. The VLC system is expected to undergo rapid progress, inspiring numerous indoor and outdoor applications; however, many technical issues need to be addressed, especially in outdoor environment. In order to provide a better understanding of the research challenges of VLC, this article presents a detailed investigation of the current state-of-art concept. Open research issues such as channel modelling and modulation techniques are also discussed, with the objective of triggering new research interest in this field. The paper also introduces our ongoing development of Wireless USB Interface and the project VIDAS.